Functional Scaffold‐Free Bone Equivalents Induce Osteogenic and Angiogenic Processes in a Human In Vitro Fracture Hematoma Model. (25th February 2021) - Pfeiffenberger, Moritz; Damerau, Alexandra; Ponomarev, Igor; Bucher, Christian H; Chen, Yuling; Barnewitz, Dirk; Thöne‐Reineke, Christa; Hoff, Paula; Buttgereit, Frank; Gaber, Timo; Lang, Annemarie
ABSTRACT: After trauma, the formed fracture hematoma within the fracture gap contains all the important components (immune/stem cells, mediators) to initiate bone regeneration immediately. Thus, it is of great importance but also the most susceptible to negative influences. To study the interaction between bone and immune cells within the fracture gap, up‐to‐date in vitro systems should be capable of recapitulating cellular and humoral interactions and the physicochemical microenvironment (eg, hypoxia). Here, we first developed and characterized scaffold‐free bone‐like constructs (SFBCs), which were produced from bone marrow–derived mesenchymal stromal cells (MSCs) using a macroscale mesenchymal condensation approach. SFBCs revealed permeating mineralization characterized by increased bone volume (μCT, histology) and expression of osteogenic markers ( RUNX2, SPP1, RANKL ). Fracture hematoma (FH) models, consisting of human peripheral blood (immune cells) mixed with MSCs, were co‐cultivated with SFBCs under hypoxic conditions. As a result, FH models revealed an increased expression of osteogenic ( RUNX2, SPP1 ), angiogenic ( MMP2, VEGF ), HIF‐related ( LDHA, PGK1 ), and inflammatory ( IL6, IL8 ) markers after 12 and 48 hours co‐cultivation. Osteogenic and angiogenic gene expression of the FH indicate the osteoinductive potential and, thus, the biological functionality of the SFBCs. IL‐6, IL‐8, GM‐CSF, and MIP‐1β were detectable within the supernatant after 24 and 48 hours of co‐cultivation. To confirm the responsiveness of our model to modifying substances (eg, therapeutics), we used deferoxamine (DFO), which is well known to induce a cellular hypoxic adaptation response. Indeed, DFO particularly increased hypoxia‐adaptive, osteogenic, and angiogenic processes within the FH models but had little effect on the SFBCs, indicating different response dynamics within the co‐cultivation system. Therefore, based on our data, we have successfully modeled processes within the initial fracture healing phase in vitro and concluded that the cross‐talk between bone and immune cells in the initial fracture healing phase is of particular importance for preclinical studies. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).